Reduced Antifungal Susceptibility of Vulvovaginal Candida Species at Normal Vaginal pH Levels: Clinical Implications. Issue 2 (April 2018) - Spitzer, Mark; Wiederhold, Nathan P.
Abstract : Objective: The aims of the study were to assess for differences in antifungal in vitro potency at pH 7 and pH 4 and to discuss any potential clinical implications of that difference. Materials and Methods: A retrospective analysis of 217 first positive yeast cultures from 217 patients. Yeast isolates underwent antifungal susceptibility testing, with minimum inhibitory concentrations (MICs) (microgram per milliliter) measured at pH 7 and pH 4 for fluconazole, itraconazole, miconazole, clotrimazole, terconazole, and nystatin. Only the first isolates collected from each patient were included in the analysis. Results: Yeast first isolates included 173 Candida albicans, 15 Candida glabrata, and 29 isolates from 8 other species. Geometric mean (GM) MIC values for all antifungals were significantly higher when tested at pH 4 ( p < .001 for all comparisons). For C. albicans, the largest GM MIC differences were observed for terconazole (0.17 pH 7 vs 6.17 pH 4) and clotrimazole (0.04 vs 0.24). For terconazole, 97.7% of the isolates had a MIC of 1 or less at pH 7 but 83.2% had a MIC of 4 or higher at pH 4. For C. glabrata, terconazole (GM MIC = 0.26 pH 7 vs >64 pH 4), clotrimazole (0.13 vs 6.96), miconazole (0.06 vs 0.76), and fluconazole (3.17 vs 26.6) were most affected. All C. glabrata isolates had a MIC of 1 or less for terconazole at pH 7 and one had a MIC of 8 at pH 4, whereas all the rest were highly resistant (MIC > 64). Conclusions: Antifungals have reduced in vitro potency when tested at lower pH. Candida glabrata is more affected than C. albicans . The impact may be greatest for the antifungal terconazole and against C. glabrata isolates.